KINEMATICS ANALYSIS OF 6 DOF INDUSTRIAL MANIPULATOR AND TRAJECTORY PLANNING FOR ROBOTIC WELDING OPERATION - Djidrov, Marjan; Doncheva, Elisaveta; Dejan Šiškovski (Faculty of Mechanical Engineering, Ss. Cyril and Methodius University in Skopje, North Macedonia, 2024)
Robotic manipulators are commonly used in the manufacturing industry for tasks such as assembly, welding, painting, and palletizing. In these applications, precise control over the position and orientation of the robot's end-effector is crucial for efficient and accurate operation. Both inverse and forward kinematics play crucial roles in the design, programming, and operation of industrial robotic manipulators, helping to ensure their effectiveness, efficiency, and safety in various manufacturing environments. In this paper the forward and inverse kinematic model of 6 degrees of freedom (DOF) industrial manipulator are presented. Additionally, the study focuses on analyzing single pass welding across a range of different scenarios. These cases involve welding paths that have different geometric shapes, with a goal to join the materials together and form a closed shape. Maintaining a vertical orientation of the welding torch was achieved, because it is important for realizing uniform heat distribution, consistent weld bead geometry, and better control over the welding process, ultimately contributing to the effectiveness of the robotic welding operation.
Keywords: robotic manipulator; forward kinematics; inverse kinematics; welding robot; manufacturing